Developing Reading Skills Picture Cards as a Learning Tool for First Grade Students at State Elementary School Number 107423 Tanjung Garbus Pagar Merbau District Deli Serdang 2023-2-24 - Rosliana Rosliana; Sutikno Sutikno (International Journal of Educational Research Excellence (IJERE), 2024)
The use of the game method will be more effective if supported by the media as a learning aid in helping grade 1 elementary school students develop reading competence. The formulation of this research problem is: How is the development of reading competence through learning media picture cards of grade I students of SD Negeri Number 107423 Tanjung Garbus, Pagar Merbau District, Deli Serdang Regency for the 2023-2024 Academic Year?". This type of research is class action research (Class Action Research) consisting of two cycles. Research procedures include planning, implementation/action, observation/evaluation, and reflection. The subjects in this study were 27 grade I students of SD Negeri Number 107423 Tanjung Garbus. If you look at cycle I and cycle II, the percentage of students who are present at the time of learning activities increases from 100%, the percentage of listening to the teacher's explanation increases from 78% to 100%, the percentage of active in asking and answering increases from 44% to 89%, the percentage of student courage in describing picture cards increases from 26% to 78%, the percentage of accuracy in using picture card media increases from 19% to 93%, The percentage of completing assignments on time from 56% to 100%, the percentage of students who do other activities during the learning process (noisy, playing, disturbing friends, in and out of class) decreased from 30% to 7%. These results show that learning using pictorial media can affect student learning motivation, effective as a tool to train student courage, effective in training student discipline in appreciating time in learning. Student learning activities affect students' ability to read.